Exploited fIShery resources of the Vembanad lake - Kurup, B Madhusoodana; Sebastian, M J; Sankaran, T M; Rabindranath, P (Indian Journal of Fisheries, 2011)
The Vembanad lake of Ketala (lat. 9°28and 10°101' and long. 76 °13' and 76 °31') is60 km long from north to south (Cochin toAlleppey) and has an area of 21 OSO ha.Thanneermukkom salinity barrier has separatedthis lake into 2 entirely different ecosystems,estuarine northern sector or thedownstream region (Cochin toThanneermukkom; Cochin backwaters area,12440 ha) and freshwater southern sectoror the upstream region (Thanneermukkomto AUeppey; area, 8610 ha). So far no concertedattempt has been made to quantify theexploited fin fish and crustacean resourcesof this lake.